Fatigue Failure Analysis of Bottom Hole Assembly during the Drilling of H-E1 and H-Q1 Wells in the Hululais Geothermal Field - Erald Eiden; Rizki Akbar; Abdul Hamid; Pri Agung Rakhmanto; Esaim Mustafa Abrahim Omar (Journal of Earth Energy Science, Engineering, and Technology, 2020)
In drilling operations it is intended to be able to conduct drilling quickly without causing damage to the drilling equipment and be able to produce good quality wells. Failure on the drilling pipe or bottom hole assembly (BHA) ranks results from loading that exceeds the maximum strength limit of the material. In this study, the calculation of the load on the downhole motor, where in the depth of the drill 512 meters failure occurs in the form of broken downhole motor. Based on the analysis conducted, at a depth of 494 meters the value of the hookload has increased quite high at 131.8 klb, while the maximum allowable hookload value is 121 klb, this indicates an overpull of 10.8 klb and based on the calculation of the drag value, a drag is obtained 38.8 klb while the maximum drag value is 28 klb, the difference between the actual drag value and the maximum allowable drag value is 10.8 klb, so it can be concluded that the failure that occurs in BHA # 10 is due to a drag that exceeds the maximum limit of 10.8 klb.